Comparative Study to Determine Antimicrobial Property of Neem Leaves (Azadirachta indica) Extracts Using Various Solvents Obtained from Two Geographical Area - S Megha; . Indradhanush; D Venkatesha (Journal of Medical Sciences and Health, 2023)
Background: Plants have been the basis for many medicinal compounds that are used in modern-day medicine, screening for medicinal plants for bioactive compounds is a way of identifying and developing new antimicrobials that are less expensive and with improved safety and efficacy. Objective: The objective of this study was to investigate the in vitro antimicrobial activity of Azadirachta indica (neem) using leaf extracts of Ethanol, Petroleum ether, and Ethyl acetate and testing them on E.coli, Klebsiella, S.aureus, MRSA and C.albicans. Materials & Methods: Minimum inhibitory concentration (MIC) was found using the serial dilution method and antimicrobial susceptibility testing (AST) was done using the disc diffusion method. Results: Ethanolic extract showed better results against Klebsiella and S.aureus, Ethyl acetate extract showed better results against E.coli and MRSA, whereas both ethanolic and petroleum ether extract showed activity against C.albicans. 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay showed that all the extracts have antioxidant property and variations were noted in the antimicrobial activity on comparing samples taken from different locations. Conclusion: Further studies are needed into the bioactive compounds of neem in order to explore their antimicrobial activity. Keywords: Antimicrobial susceptibility, Azadirachta indica, Ethanol, Ethyl acetate, Disc diffusion, MIC, Petroleum ether